Addressing Adolescent Bullying: The Role of Restorative Practices and SEL Across Diverse Educational Contexts - Rizqi , Putri Umrotur (Sinergi International Journal of Psychology, 2024)
Bullying among adolescents remains a pervasive global issue with significant psychological, social, and academic consequences. This study examines the role of self-esteem, social support, and systemic factors in influencing bullying behaviors. A comprehensive literature review was conducted using Scopus, Google Scholar, and PubMed, with studies selected based on inclusion criteria focusing on bullying prevalence, intervention strategies, and mental health outcomes. The findings indicate that strong social networks and high self-esteem serve as protective factors against both victimization and perpetration. Additionally, school climate and cultural influences play crucial roles in shaping bullying dynamics. Restorative practices and social-emotional learning (SEL) programs have shown promise in reducing bullying incidents, particularly when integrated into school curricula and community-based initiatives. However, geographical and socioeconomic disparities affect the accessibility and effectiveness of these interventions. This study underscores the need for targeted policies, including teacher training, parental engagement, and digital literacy programs, to combat traditional and cyberbullying effectively. Future research should explore longitudinal impacts of bullying interventions and their adaptability across different cultural and economic contexts. Addressing these gaps will contribute to the creation of safer educational environments and improved adolescent mental health outcomes.